Violence Against Women and Girls : Citizen Security, Law, and Justice Brief - Gennari, Floriza; Hidalgo, Nidia; McCleary-Sills, Jennifer; Arango, Diana (World Bank, Washington, DC, 2015)
For every three years a country is affected by major violence (defined as deaths due to war or excess homicides comparable to a major war), economic growth lags behind by 2.7 percentage points. Citizen security issues impact women and men differently. For example, women are more likely to be assaulted or murdered by someone they know - in fact, worldwide the share of homicides by an intimate partner was six times higher for female victims compared with male victims (39 percent versus 6 percent, respectively). Boys who witness intimate partner violence (IPV) during childhood are more likely to exhibit delinquent behavior and to perpetrate IPV in adulthood. And girls who witness violence are more likely to experience IPV in adulthood.